Methods for truck dispatching in open-pit mining. - Guilherme Sousa Bastos (2010)
Material transportation is one of the most important aspects of open-pit mine operations. The problem usually involves a truck dispatching system in which decisions on truck assignments and destinations are taken in real-time. Due to its significance, several decision systems for this problem have been developed in the last few years, improving productivity and reducing operating costs. As in many other real-world applications, the assessment and correct modeling of uncertainty is a crucial requirement as the unpredictability originated from equipment faults, weather conditions, and human mistakes, can often result in truck queues or idle shovels. However, uncertainty is not considered in most commercial dispatching systems. In this thesis, we introduce novel truck dispatching systems as a starting point to modify the current practices with a statistically principled decision making methodology. First, we present a stochastic method using Time-Dependent Markov Decision Process (TiMDP) applied to the truck dispatching problem. In the TiMDP model, travel times are represented as probabilistic density functions (pdfs), time-windows can be inserted for paths availability, and time-dependent utility can be used as a priority parameter. In order to minimize the well-known curse of dimensionality issue, to which multi-agent problems are subject when considering discrete state modelings, the system is modeled based on the introduced single-dependent-agents. Based also on the single-dependent-agents concept, we introduce the Genetic TiMDP (G-TiMDP) method applied to the truck dispatching problem. This method is a hybridization of the TiMDP model and of a Genetic Algorithm (GA), which is also used to solve the truck dispatching problem. Finally, in order to evaluate and compare the results of the introduced methods, we execute Monte Carlo simulations in a example heterogeneous mine composed by 15 trucks, 3 shovels, and 1 crusher. The uncertain aspect of the problem is represented by the path selection through crusher and shovels, which is executed by the truck driver, being independent of the dispatching system. The results are compared to classical dispatching approaches (Greedy Heuristic and Minimization of Truck Cycle Times - MTCT) using Student's T-test, proving the efficiency of the introduced truck dispatching methods.